A Comprehensive Disclosure Model in Iranian Commercial Insurance Companies Centered on International Financial Reporting Standards Using a Multi-Grounded Theory Approach - Rahmaninia, Javad; Fazeli, Naghi; Khosravani, Arzoo (Management Strategies and Engineering Sciences, 2026)
Voluntary disclosure of information is an indirect mechanism through which International Financial Reporting Standards (IFRS) generate benefits for capital markets. Managers typically employ voluntary disclosure as a substitute for mandatory reporting, thereby conveying confidential company performance information to investors. The aim of this study is to present a comprehensive disclosure model for Iranian commercial insurance companies, focusing on IFRS and utilizing the multi-grounded theory approach. The first step involves formulating research questions based on the dimensions of grounded theory. In the second step, the researcher systematically reviews published articles in reputable domestic and international scientific journals to identify credible and valid documents within an appropriate time frame. Initially, related keywords—both individually and in combination—were examined in Persian and English for the period 2013 to 2024, and for English-language articles from 1980 to 2024. As a result, 27 relevant articles were identified. Since data collection in the grounded theory approach is based on theoretical sampling, in this study, data were synthesized through meta-combination, followed by in-depth interviews. Subsequently, using grounded theory and integrating it through the multi-grounded approach, a comprehensive model for identifying the disclosure framework was developed. Reporting and information disclosure are the most critical tools companies use to communicate with shareholders. When information disclosure is mandated by a regulatory or legislative authority, it is referred to as mandatory disclosure. In contrast, if the disclosure is not influenced by specific regulations and is conducted voluntarily by the company, it is considered voluntary disclosure. The voluntary disclosure theory posits that managers will disclose company information under their control if the benefits of such disclosure outweigh the associated costs.